1985
DOI: 10.1530/acta.0.1090281
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of individual compartments of the genital tract to oestrogen and testosterone concentrations in ejaculates of the boar

Abstract: The investigation of steroids in compartments of the genital tract of boars revealed that in the tubular fluid a pattern apparently exists which is unique in this compartment. It is characterized by high concentrations of unconjugated testosterone (35 ng/ml) and even higher amounts of oestradiol-17\g=b\(42.6 ng/ml) whereas in other compartments oestrone is the predominant oestrogen. At least in the ejaculate half of the total amount of oestrogens is bound to sperms and it is concluded that sperms act as a carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 7 publications
1
27
0
Order By: Relevance
“…Similar results were obtained by Rostalski (2005) and Hoffmann et al (2010). In contrary, Claus et al (1983Claus et al ( , 1985 found higher concentrations of unconjugated oestrogens in seminal plasma compared to blood plasma. Oestrogens from boar semen increase the myometrial contraction frequency in the sows by stimulation of PGF2α release (Claus et al 1987, Claus 1990).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results were obtained by Rostalski (2005) and Hoffmann et al (2010). In contrary, Claus et al (1983Claus et al ( , 1985 found higher concentrations of unconjugated oestrogens in seminal plasma compared to blood plasma. Oestrogens from boar semen increase the myometrial contraction frequency in the sows by stimulation of PGF2α release (Claus et al 1987, Claus 1990).…”
Section: Discussionsupporting
confidence: 88%
“…Concentrations of oestrogens in the blood plasma of mature boars are high and exceed those found in sows during oestrus (Claus and Hoffmann 1980, Claus et al 1983, 1985. However, little is known about their concentrations in blood plasma and seminal plasma during the early postpuberal period in the boar.…”
Section: +mentioning
confidence: 99%
“…The intra-assay coefficient of variation varied between 3.9 and 6.7% depending on concentration and for the interassay coefficient of variation varied between 7 and 18%. Total estrogens (Claus et al 1985) were determined with an antiserum which had been raised against estrone-17-CMO-BSA. It was used at a dilution in the ratio of 1:15 000.…”
Section: Hormone Analysismentioning
confidence: 99%
“…The sensitivity was 73.5 pmol/l plasma, the intra-assay coefficient of variation varied between 2.9 and 3.7% and the interassay coefficient of variation varied between 10.7 and 16%. In addition to total estrogens, the concentrations of 17b-estradiol were determined in two randomly selected male fetuses from weeks 10, 13, and 15 (Claus et al 1985). The antiserum had been raised against 17b-estradiol-6-CMO-BSA.…”
Section: Hormone Analysismentioning
confidence: 99%
“…Furthermore, boar testes secrete large quantities of estrogens, wherein plasma estradiol-17b (E 2 ) levels increase in a stepwise fashion during pubertal development (Allrich et al 1982, Schwarzenberger et al 1993, Estienne et al 2000. In addition, an androgen-binding protein expressed by Sertoli cells could not be identified (Jegou & Le Gac-Jegou 1978), but testosterone concentrations in the tubular fluid are high (Claus et al 1985). Despite accumulating data on boars, there has been very little progress in understanding the function of INSL3, even though INSL3 was first discovered in the boar testis.…”
Section: Introductionmentioning
confidence: 99%